Estimation Of The Shelf Life Of Mackerel Tuna Sausage With The Addition Of Basil Leaf Extract Using The Aslt Method - Ilyas Ilyas Juliansyah; Mae Amelianawati; Saepul Adnan (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose: This study aimed to estimate the shelf life of mackerel tuna sausage (Euthynnus affinis) supplemented with basil leaf extract (Ocimum basilicum L.) using the Accelerated Shelf Life Test (ASLT) method with the Arrhenius approach based on protein content and sensory quality parameters. Methodology: The product was stored at -15°C, 5°C, 25°C, and 35°C for 15 days with observations conducted every 3 days. Protein content was determined using the Kjeldahl method, while sensory quality was evaluated through hedonic testing. Data were analyzed using zero-order and first-order kinetic models and subsequently processed using the Arrhenius equation to estimate product shelf life. Results: The results indicated that increasing storage temperature accelerated the decline in protein content and sensory quality of mackerel tuna sausage, whereas lower temperatures were more effective in preserving product quality. Findings: Storage temperature significantly influenced the deterioration rate of the product, with higher temperatures causing a faster reduction in product quality. Novelty: The novelty of this study lies in the application of basil leaf extract as a natural antioxidant in mackerel tuna sausage and the simultaneous use of protein and sensory parameters in shelf-life prediction through the ASLT-Arrhenius approach. Originality: The originality of this research is demonstrated by the combination of basil leaf extract and vacuum packaging, which effectively slowed product deterioration during storage. Conclusion: The estimated shelf life of mackerel tuna sausage supplemented with basil leaf extract was 43 days at -15°C and 35 days at 5°C, indicating that low-temperature storage is recommended to maintain product quality and extend shelf life. Paper Type: Experimental research article.